Genetics of ataxia telangiectasia in a highly consanguineous population. (28th September 2021) - Al‐Muhaizea, Mohammed A.; Aldeeb, Hanouf; Almass, Rawan; Jaber, Hadeel; Binhumaid, Felwa; Alquait, Laila; Abukhalid, Musaad; Aldhalaan, Hesham; Alsagob, Maysoon; Al‐Bakheet, Albandary; Aldosary, Mazhor; Alkofide, Hadeel; et al.
Abstract: Ataxia telangiectasia (AT) is a rare autosomal recessive multisystemic disorder. It usually presents in toddler years with progressive ataxia and oculomotor apraxia, or less commonly, in the late‐first or early‐second decade of life with mixed movement disorders. Biallelic mutations in ataxia telangiectasia mutated gene ( ATM ) cause AT phenotype, a disease not well documented in Saudi Arabia, a highly consanguineous society. We studied several Saudi AT patients, identified ATM variants, and investigated associated clinical features. We included 17 patients from 12 consanguineous families. All patients had comprehensive clinical and radiological assessment, and most were examined through whole‐exome sequencing (WES). Selected individuals were analyzed using various genetic approaches. We identified five different ATM variants in our patients: three previously reported mutations, and two novel variants. Nearly all patients had classical AT presentation except for two patients with a milder phenotype. Among the three known variants, a deletion causing truncation (c.381delA resulting in p.(Val128Ter)) was identified in 13 patients. Two patients harboured the other two truncating variants, (c.9001_9002delAG resulting in p.Ser3001Phefs*6) and (c.9066delA resulting in p.Glu3023Alafs*10) and two patients had novel compound heterozygous variants (NM_000051.3:Paternal Allele:c.8762C > G;p.Thr2921Arg and Maternal Allele:c.1057T > C;p.Cys353Arg). We speculate that c.381delA is a founder mutation in our population. This study provides a genotype–phenotype relationship in a previously unstudied consanguineous population. Our findings contribute to improve local clinical care, therapy, and genetic counseling.